Integrating the Philosophy of Nggahi Rawi Pahu in Early Childhood Education Management: An Ethnopedagogical Approach in Dompu Regency, Indonesia - Ihlas Ihlas; Amma Ainun; Moses Adeleke Adeoye (IJECA (International Journal of Education and Curriculum Application), 2026)
This study investigates the integration of the local philosophical value “Nggahi Rawi Pahu” into the management of Early Childhood Education (ECE) through an ethnopedagogical approach in Dompu Regency, Indonesia. In the context of accelerating globalization, early childhood education faces increasing challenges in maintaining cultural relevance, often resulting in the marginalization of local wisdom. This research is therefore significant as it seeks to reposition indigenous values as a foundational element in shaping children’s character, social awareness, and cultural identity from an early age. The study aims to explore how “Nggahi Rawi Pahu” is conceptualized and operationalized within ECE management practices and to examine its pedagogical implications. Employing a qualitative research design, data were collected through in-depth interviews, participatory observations, and document analysis involving teachers, school principals, parents, and community leaders. The data were analyzed using thematic analysis to uncover patterns of meaning and forms of value integration across educational processes. The findings demonstrate that “Nggahi Rawi Pahu”, which embodies principles of harmony, mutual respect, responsibility, and collective solidarity, is not merely symbolically acknowledged but substantively integrated into learning planning, classroom interactions, and institutional culture. The novelty of this study lies in showing that local wisdom is used as a practical teaching framework, not just as cultural knowledge, and plays a direct role in shaping students’ character and learning behavior. Teachers function as cultural agents who translate abstract philosophical values into concrete pedagogical practices, thereby fostering a culturally responsive learning environment. These findings suggest that the integration of local wisdom through ethnopedagogical strategies strengthens the relevance and transformative capacity of ECE management. The study offers a conceptual contribution by articulating a culturally grounded model of early childhood education that is both context-sensitive and globally relevant.